Practices and drivers of self-medication with antibiotics among undergraduate medical students in Eastern Uganda: A cross-sectional study - Nakato, Gloria; Adongo, Pamella R.; Iramiot, Jacob Stanley; Epuitai, Joshua (Plos one, 2023)
Self-medication with antibiotics remains one of the major drivers of antimicrobial resistance. Practices of self-medication among nursing and medical students have not been explored in our setting. This study sought to determine the prevalence and factors associated with self-medication with antibiotics among undergraduate university students pursuing health-related courses in Eastern Uganda. A descriptive cross-sectional study design was used. The study was done among undergraduate students who were doing undergraduate programs in Nursing, Anesthesia, and medicine at Busitema University. A self-administered questionnaire was used to collect data from 326 participants. Descriptive statistics were used in data analysis. The prevalence of self-medication with antibiotics was 93.8% (n = 300) of which 80% were either currently using self-medication or had self-medicated in the past six months. The common reasons for self-medication were the perception that it was a minor illness (55%), previous use of antibiotic (52%), a perception that they were health workers (50%), and the notion that they knew the right antibiotic for their condition (44%). Metronidazole (64%) and amoxicillin (65%) were the most commonly used antibiotics. Self-medication was most common for conditions such as peptic ulcer, diarrhea, and wound infections. Inappropriate drug use was common among participants on self-medication which occurred in the form of multiple use of antibiotics (64.4%, n = 194) and a tendency to switch to other antibiotics (58.5%) mostly because the former antibiotic was perceived not to be an effective treatment. The prevalence of self-medication with antibiotics was high among medical students. Prior use of the antibiotic and having a minor illness were the most common drivers of self-medication. Public health strategies should address the high misuse of antibiotics among medical students to negate the likely consequence of antimicrobial resistance.